‘This Could Be Me’: Law Students’ Experiences of a Rural, Regional, Remote (RRR) Clinical Program - Tamara Walsh (Legal Education Review)
This article describes a rural, regional, remote (RRR) clinical legal education program that was piloted in Queensland. Nine students attended four regional community legal centres during the summer and winter break of 2024 for two weeks. The students were interviewed upon their return. Students suggested that their RRR practise intentions had increased as a result of the placement – many said they could now see themselves working in RRR areas upon graduation, others said they were now considering working in a community legal centre. It seemed that their positive experiences on placement, particularly the commitment, friendliness and warmth of their supervisors, influenced their attitudes towards RRR legal practice.